Comparing Clinical Efficacy between Minimally Invasive Osteotomy and Weil Osteotomy for Treatment of Metatarsalgia - Zixing Bai; Xuhan Cao; Yanjun Yang; Chengyi Sun; Si Chen; Haiwei Hu; Jianmin Wen; Xinxiao Lin; Weidong Sun (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Both minimally invasive osteotomy and Weil osteotomy can effectively relieve pain symptoms of metatarsal pain, but their indications and clinical efficacy lack data support. Aim and objective: To investigate the differences of indications and clinical efficacy between the minimally invasive osteotomy and the Weil osteotomy for treatment of the metatarsalgia. Materials and methods: One hundred and four metatarsal bones in 64 feet of 51 patients with mild metatarsalgia were divided into two groups. The minimally invasive osteotomy and elevation of metatarsal operation were performed on the 24 patients in group I, a total of 55 metatarsal bones of 26 feet. The Weil osteotomies were performed on the 27 patients in group II, a total of 49 metatarsal bones of 38 feet. The visual analog scale/score (VAS), the American College of Foot and Ankle Surgeons (ACFAS), the maximum plantar force, the peak pressure, and the force-time integrals of the target metatarsals were compared between preoperation and postoperation, respectively. Results: All test data, such as the VAS, the ACFAS, the maximum plantar force, the peak pressure, and the force-time integrals under the target metatarsal heads after osteotomy, were significantly different (p < 0.05) from those before osteotomy in both groups. However, all the above data were not significantly different between the two groups (p > 0.05). Four metatarsals were reported to have a delayed bone healing after the minimally invasive osteotomy. Conclusion: Both osteotomies can effectively release the pain. The minimally invasive osteotomy is easy to handle and has the advantages such as less complication, low cost, and a low requirement on equipment, which can be suggested to be widely used in the basic level hospital.